Effects of bio-inspired infill design on the mechanical properties of ultrasonic vibration assisted 3D printed samples - Maidin, Shajahan; Shahrum, Mohd Afiq; Rajendran, Thavinnesh Kumar; Ismail, Shafinaz (https://iopscience.iop.org/article/10.1088/2631-8695/ad51d6/pdf, 2024)
This paper study the tensile strength and microstructure of the 3D bio-inspired printed samples by comparing the ultrasonic vibration assisted test samples with standard ABS and PLA samples with three different bio-inspired infill designs namely elephant trunk, bamboo and leaf. The test samples were printed with optimal printing process parameters and 0 kHz and 20 kHz frequency of ultrasonic vibration. SolidWorks software was used to design the bio-inspired infill designs and create the 3Dprinted test samples. Tests to evaluate mechanical properties and microstructure were carried out after printing the test samples. The investigation primarily focuses on the impact of ultrasonic vibration assisted 3D bio-inspired printed samples of ABS and PLA materials. This research explores using ultrasonic vibration assistance to enhance the tensile strength of 3D-printed infills. The elephant trunk inspired infill design with ABS at 20 kHz achieved the best results, suggesting that ultrasonic vibration strengthens intermolecular bonding. The bamboo inspired infill performed poorly due to its design, while PLA deformed due to lower heat resistance. Overall, ultrasonic frequency improved layer bonding, especially for the elephant trunk infill, indicating potential for further optimization. These results demonstrate the effectiveness of bio-inspired infill solutions, mainly the ABS elephant trunks with ultrasonic 20 kHz of vibration.